A remote sensing approach to assess the historical invasion of Phragmites australis in a brackish coastal marsh - Hagani, Jason S.; Takekawa, John Y.; Chappell, Steven C.; Tanner, Richelle L.; Ernst, Adrienne R.; Kettenring, Karin M. (Frontiers in Ecology and Evolution, 2023)
Coastal estuarine wetlands provide important habitats for a variety of endemic flora and fauna but are particularly vulnerable to biological invasions. Regular monitoring of changes in these vulnerable wetlands has become increasingly important for effective management, especially considering threats from climate change effects and human disturbance. Historical analyses of plant invasions may guide targeted management strategies to eradicate harmful species. With the improved availability of high-resolution data and innovations in remote sensing, estimating the distribution of invasive species has never been more accessible. We assessed the spread of non-native Phragmites australis subsp. australis in Suisun Marsh on the upper San Francisco Estuary, one of the largest brackish coastal wetlands in North America. Suisun Marsh consists of managed and tidal wetlands, and efforts have been made to control invasive P. australis on the managed wetlands to support habitat value for wildlife. We used remote-sensing analyses of publicly available, biennial color-infrared images taken by the National Agriculture Imagery Program (NAIP) to map the expansion of invasive P. australis across two decades. We generated random forest classifications of representative images to map the distribution of P. australis, then calculated a variety of metrics describing the rate and spatial extent of the P. australis spread. Additionally, we ran generalized linear models to examine factors related to the growth of P. australis. Our classifications yielded accuracies of over 90% and showed a 234% (1084 ha) increase in P. australis between 2003 and 2018. The expansion rate of P. australis patches averaged 1.32 m/yr (+0.53 SD) which is higher than most reported in the literature. We found that P. australis expansion in managed areas within levees was significantly correlated with invasion in tidal areas outside the levees on the same parcel and also related to its spread on adjacent parcels. Our findings suggest that despite individual landowner management efforts, P. australis has continued to expand substantially throughout Suisun Marsh. Future efforts to treat invasive P. australis may require emphasizing adaptive, collaborative management rather than individual management strategies to ensure the invasive species is eradicated on a large scale to preserve the valued ecosystem functions.